Beta-Hemolytic Streptococcal Infective Endocarditis: Characteristics and Outcomes From a Large, Multinational Cohort. (10th April 2020) - Fernández Hidalgo, Núria; Gharamti, Amal A; Aznar, María Luisa; Almirante, Benito; Yasmin, Mohamad; Fortes, Claudio Querido; Plesiat, Patrick; Doco-Lecompte, Thanh; Rizk, Hussein; Wray, Dannah; Lamas, Cristiane; Durante-Mangoni, Emanuele; et al.
Abstract: Background: Beta-hemolytic streptococci (BHS) are an uncommon cause of infective endocarditis (IE). The aim of this study was to describe the clinical features and outcomes of patients with BHS IE in a large multinational cohort and compare them with patients with viridans streptococcal IE. Methods: The International Collaboration on Endocarditis Prospective Cohort Study (ICE-PCS) is a large multinational database that recruited patients with IE prospectively using a standardized data set. Sixty-four sites in 28 countries reported patients prospectively using a standard case report form developed by ICE collaborators. Results: Among 1336 definite cases of streptococcal IE, 823 were caused by VGS and 147 by BHS. Patients with BHS IE had a lower prevalence of native valve ( P < .005) and congenital heart disease predisposition ( P = .002), but higher prevalence of implantable cardiac device predisposition ( P < .005). Clinically, they were more likely to present acutely ( P < .005) and with fever ( P = .024). BHS IE was more likely to be complicated by stroke and other systemic emboli ( P < .005). The overall in-hospital mortality of BHS IE was significantly higher than that of VGS IE ( P = .001). In univariate analysis, variables associated with in-hospital mortality for BHS IE were age (odds ratio [OR], 1.044; P = .004), prosthetic valve IE (OR, 3.029; P = .022), congestive heart failure (OR, 2.513; P = .034), and stroke (OR, 3.198; P = .009). Conclusions: BHS IE is characterized by an acute presentation and higher rate of stroke, systemic emboli, and in-hospital mortality than VGS IE. Implantable cardiac devices as a predisposing factor were more often found in BHS IE compared with VGS IE.